PENGARUH MEDIA SMART BOX TERHADAP PEMAHAMAN KONSEP SISWA PADA MATA PELAJARAN IPAS KELAS IV SD INPRES PARE’-PARE', KABUPATEN GOWA. - Kurnia Utami; Latri; Siti Zahra Mulianti Natsir (STKIP Subang, 2026)
This study aims to determine the description of the use of Smart Box media in science learning, students' understanding of science concepts on the material of the state of matter and its changes, and the effect of the use of Smart Box media on the understanding of science concepts of fourth-grade students of SD Inpres Pare'-Pare', Gowa Regency. This study is an experimental study with a quantitative approach using a Quasi Experiment design of the Pretest-Posttest Control Group Design. The study population was all fourth-grade students of SD Inpres Pare'-Pare', Gowa Regency. The study sample consisted of 29 students in the experimental class and 29 students in the control class selected using a purposive sampling technique. Research data were collected through observation sheets of learning implementation and student learning outcome tests. Data were analyzed using descriptive and inferential analysis. The results showed that the implementation of learning using Smart Box media was in the very good category. In addition, students' understanding of science concepts on the material of the state of matter and its changes increased. This is indicated by the posttest scores of students in the experimental class which were higher than those in the control class. Thus, it can be concluded that the use of Smart Box media has an effect on the understanding of science concepts of fourth-grade students of SD Inpres Pare'-Pare', Gowa Regency.